Liveability Considerations: Towards Designing Sustainable Public Housing in Niger State, Nigeria - Haruna, Paul Baba; Zubairu, Stella; Olagunju, Remi Ebenezer; Akande, Oluwafemi Kehinde (Journal of Contemporary Urban Affairs, 2023)
This study investigates liveability in the context of sustainable public housing in Niger State, Nigeria, where existing housing efforts have fallen short of residents' satisfaction. Recognizing the critical link between liveability indicators and environmental sustainability, this research aims to identify key liveability variables that could be integrated into the design and construction of sustainable public housing. Employing a mixed-method approach, the study involved cluster sampling for selecting housing estates and units, followed by the administration of 910 questionnaires containing 102 questions on liveability variables. Analytical techniques, including Hierarchical Cluster Analysis, Factor Analysis, and Multiple Regression Analysis, were used to group, refine, and validate the liveability variables. The results revealed 21 significant variables that collectively could achieve a 92.9% satisfaction rate among residents if incorporated into public housing design. These findings underline the potential of addressing liveability in the pursuit of sustainable housing solutions, offering insights for urban planners, architects, and policymakers. By focusing on the residents' perspectives, the study contributes to a more user-centred approach in public housing development, promoting long-term satisfaction and reducing the need for post-occupancy alterations.